Excellent ONO passivation on phosphorus and boron diffusion demonstrating a 25% efficient IBC solar cell. (10th July 2020) - Kho, Teng Choon; Fong, Kean Chern; Stocks, Matthew; McIntosh, Keith; Franklin, Evan; Phang, Sieu Pheng; Liang, Wensheng; Blakers, Andrew
Abstract: This work presents results of a laboratory‐scale interdigitated back contact (IBC) solar cell with an independently measured efficiency of 25.0%, featuring open‐circuit voltage of 716 mV, short‐circuit current of 43.0 mA.cm −2 and fill factor of 81.0%. Notably, the high efficiency was achieved based on significant improvements resulting from the optimised cell structure, excellent SiO2 ‐SiNx ‐SiOx (ONO) surface passivation, detailed bulk lifetime management strategy and improved random pyramid texturing. Experimental details and analysis of the individual improvements over prior work are presented in‐depth. Abstract : We present excellent surface passivation using SiO2 ‐SiNx ‐SiOx (ONO) stack on phosphorus and boron‐diffused surfaces. The surface passivation was optimised and implemented onto an interdigitated back contact (IBC) solar cell with refined fabrication design and process to achieve a certified cell efficiency of 25.0%.